2017
DOI: 10.1111/jerd.12286
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Shade‐Matching Training Program on the Dentists' Ability to Match Teeth Color

Abstract: Visual shade matching is currently the most frequently applied clinical method for shade matching. Assessing colors and matching shades are vital steps in aesthetic dentistry. In the absence of knowledge, shade-matching skills cannot be mastered effectively. Clinicians can improve their ability to differentiate colors through a short training regimen. Being aware of the whole process of assessing color and the factors affecting shade-matching practice will lead to a significant improvement in the ability to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…Educational level, along with training on shade matching, exhibits a significant role in shade matching accuracy. Earlier studies have indicated that to improve shade-matching performance, dental practitioners must be participated in practical courses, ongoing education strategies, and further teaching classes [42]. As far as the present study is concerned, a significant difference was evident between all shade tabs under correcting light among clinical and non-clinical students (p < 0.05) thereby proving clinical experience of students on color matching leads to enhancing the accuracy of shade selection.…”
Section: Discussionsupporting
confidence: 50%
“…Educational level, along with training on shade matching, exhibits a significant role in shade matching accuracy. Earlier studies have indicated that to improve shade-matching performance, dental practitioners must be participated in practical courses, ongoing education strategies, and further teaching classes [42]. As far as the present study is concerned, a significant difference was evident between all shade tabs under correcting light among clinical and non-clinical students (p < 0.05) thereby proving clinical experience of students on color matching leads to enhancing the accuracy of shade selection.…”
Section: Discussionsupporting
confidence: 50%
“…50,51 Thus, improving shade matching skills by intensive education and training is strongly recommended. 83,91,[132][133][134][135][136] Also, using evidence-based shade guides and light conditions is advocated for low-skilled dentists. and most of all acceptable accuracy and precision.…”
Section: Accuracy and Precision Of Visual Methodsmentioning
confidence: 99%
“…Among the aforementioned factors, the observer experience has the greatest impact on the accuracy/precision of visual method, 88,131 while factors such as shade guide and light condition become more prominent for inexpert observers 50,51 . Thus, improving shade matching skills by intensive education and training is strongly recommended 83,91,132–136 . Also, using evidence‐based shade guides and light conditions is advocated for low‐skilled dentists 52,53,121 …”
Section: Visual Methodsmentioning
confidence: 99%
“…This finding agrees with previous studies that suggested using the middle region of the tabs for shade matching. 34 This might be attributed to the relatively flat design of the tab in the middle region as opposed to the curved surfaces of the incisal and the cervical regions.…”
Section: Discussionmentioning
confidence: 99%